Chemistry in Second Life - Lang, Andrew SID; Bradley, Jean-Claude (Springer Open, 2009)
This review will focus on the current level on chemistry research, education, and visualization possible within the multi-user virtual environment of Second Life. We discuss how Second Life has been used as a platform for the interactive and collaborative visualization of data from molecules and proteins to spectra and experimental data. We then review how these visualizations can be scripted for immersive educational activities and real-life collaborative research. We also discuss the benefits of the social networking affordances of Second Life for both chemists and chemistry students.
The authors would like to thank Joanna Scott and Nature who provided the initial land in Second Life which led to the authors meeting and eventual collaboration, Kate Sellar and the American Chemical Society who provided the land where a number of the tools were created; Sandy Adam of Aldrich Chemical, Peter Miller of the University of Liverpool, David Reeves of Yeshiva University, Joan Slonczewski of Kenyon College, David Wild of Indiana University, Rajarshi Guha at the National Institutes of Health, Antony Williams of ChemSpider, Eloise Pasteur, and Beth Ritter-Guth who all contributed their time and expertise at various points during the author's collaboration.